PENGARUH CHANGE MANAGEMENT MODEL ADKAR TERHADAP KINERJA PEGAWAI BALAI BESAR WILAYAH SUNGAI PEMALI JUANA - Putri Syaharani, Shabilla; Kismartini, Kismartini; Suwitri, Sri (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2024)
Employee performance refers to the achievement of employee goals and responsibilities in an organization. In carrying out its duties and authority, there are still complaints from the public regarding the services provided by the Pemali Juana River Regional Office. Apart from that, it was also found that there were actual activities that were not in accordance with the proper targets, which indicated that employee performance was still not optimal. Therefore, employee performance must always be improved in order to create good public services for the community. This research aims to analyze the influence of awareness, desire, knowledge, ability, and reinforcement on employee performance. Carried out through explanatory research with a total of 85 respondents, data collection was carried out using a questionnaire with a Likert scale and analyzed through descriptive analysis, validity test, reliability test, classical assumption test and multiple linear regression. The findings show that there is a significant positive influence between the ADKAR model variables and employee performance, with awareness showing the highest influence at 51.9%, desire at 21.5%, knowledge at 35%, ability at 43.7%, and reinforcement at 22% . Suggestions from this research improve the strengthening strategy in the ADKAR model to ensure successful implementation of sustainable change. In addition, it provides training to employees on time management, problem solving, and skills relevant to their duties.